2023
DOI: 10.1038/s41598-023-35242-0
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenergic stimulation of α1 adrenoceptors in the medial prefrontal cortex mediates acute stress-induced facilitation of seizures in mice

Abstract: Stress is one of the critical facilitators for seizure induction in patients with epilepsy. However, the neural mechanisms underlying this facilitation remain poorly understood. Here, we investigated whether noradrenaline (NA) transmission enhanced by stress exposure facilitates the induction of medial prefrontal cortex (mPFC)-originated seizures. In mPFC slices, whole-cell current-clamp recordings revealed that bath application of picrotoxin induced sporadic epileptiform activities (EAs), which consisted of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, new pyrrolidin-2-one derivatives with affinity for α 1 -ARs cause a decrease in seizure susceptibility by exhibiting GABAergic activity ( 77 ). In addition, it has been shown that seizures originating from the medial prefrontal cortex and caused by acute stress are induced by NE stimulation of α 1 -ARs ( 65 ). Electrophysiological recordings have revealed that NE promotes epileptiform activity induction through α 1- AR stimulation in medial prefrontal cortex pyramidal cells.…”
Section: Effects Of α 1 -Adrenergic Receptors On E...mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, new pyrrolidin-2-one derivatives with affinity for α 1 -ARs cause a decrease in seizure susceptibility by exhibiting GABAergic activity ( 77 ). In addition, it has been shown that seizures originating from the medial prefrontal cortex and caused by acute stress are induced by NE stimulation of α 1 -ARs ( 65 ). Electrophysiological recordings have revealed that NE promotes epileptiform activity induction through α 1- AR stimulation in medial prefrontal cortex pyramidal cells.…”
Section: Effects Of α 1 -Adrenergic Receptors On E...mentioning
confidence: 99%
“…α 1 -ARs frequently increase the activity of GABAergic interneurons, and GABA released from interneurons plays a key role in the inhibitory effects of these receptors (59,60). By contrast, the overactivity of α 1B -AR causes spontaneous epileptic seizures in mice overexpressing α 1B -AR (61), while a deficiency in α 1B -AR results in the reduction of pilocarpine-induced seizures (31) (Table I) (30,31,(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73).…”
Section: Effects Of α 1 -Adrenergic Receptors On Epilepsymentioning
confidence: 99%